Copepod feeding response to varying Alexandrium spp. cellular toxicity and cell concentration among natural plankton samples - Teegarden, Gregory J.; Campbell, Robert G.; Anson, Dean T.; Ouellett, Aaron; Westman, Benjamin A.; Durbin, Edward G. (Harmful Algae, 2008)
We challenged four species of copepod grazers (Acartia hudsonica, Centropages hamatus, Eurytemora herdmani, Calanus finmarchicus) with natural water samples containing non-toxic algae mixed with one of three clones of Alexandrium spp.-A. tamarense GTCN16 (non-toxic), A. fundyense GTCA28 (moderate toxicity), and A. fundyense BC1 (higher toxicity), each at relatively high (105 cells L-1) and low (104 cells L-1) concentrations. Within any one copepod species, significant differences existed in copepod clearance rates and total food ingested between high and low Alexandrium cell concentrations, and between levels of toxicity, but feeding response did not follow a predictable relationship proportional to toxin levels-rather, the presence or absence of toxin was more important than the level of toxicity. C. finmarchicus behaved differently from the smaller coastal copepods, showing less selectivity and greater concentration dependence. In low Alexandrium concentration treatments, copepod clearance rates on Alexandrium were usually higher, and electivity indices for Alexandrium less negative (indicating less avoidance), compared to high concentration treatments. In high toxicity (BC1) treatments of all copepod species (except C. finmarchicus), total food consumption was consistently less at high Alexandrium concentrations compared to low concentrations, suggesting that high toxicity and concentration suppress overall feeding, while in non-toxic (GTCN 16) treatments total consumption was always higher at high Alexandrium concentrations. Copepod grazers do not follow predictable feeding rules throughout a continuum of conditions, but become more predictable at extremes of concentration and toxicity of prey, consistent with the conclusion that both factors are important. Results support the hypothesis that grazer deterrence imparted by toxicity is only effective at high cell concentrations, but even then will not protect against all grazers. © 2007 Elsevier B.V. All rights reserved.